Clinical Features and Endoscopic Treatment of Chinese Patients With Hereditary Pancreatitis. Issue 1 (January 2015) - Sun, Xiao-Tian; Hu, Liang-Hao; Xia, Tian; Shi, Lin-Li; Sun, Chang; Du, Yi-Qi; Wang, Wei; Chen, Jian-Min; Liao, Zhuan; Li, Zhao-Shen
<x xml:space="preserve">Abstract</x> Objectives Hereditary pancreatitis (HP) has been rarely investigated in China. We aimed to describe clinical features and mutation frequency of Chinese patients with HP and to evaluate outcomes of endoscopic treatments. Methods Inpatients diagnosed with HP from January 1995 to March 2013 were included. Demographic and clinical data including first onset age, age at diagnosis, sex, main symptoms, radiological findings, and outcomes of endoscopic treatments were collected. Mutations in serine protease inhibitor Kazal type 1 (SPINK1), PRSS1, and cystic fibrosis transmembrane conductance regulator (CFTR) were analyzed. Results A total of 22 inpatients with HP (male, 12; female, 10) participated in this study. Mean (SD) age at first onset and at diagnosis were 24.5 (11.9) years and 29.1 (11.2) years, respectively. The predominant radiological feature was pancreatic calcifications. Thirty-nine endoscopic retrograde cholangiopancreatography procedures were successfully performed on 19 cases. In the final long-term follow-up, 21 patients got complete or incomplete remission after endoscopic retrograde cholangiopancreatography and/or surgery. Genetic analyses were available in 20 patients, and mutation rates of R122H, N29I, and A16V in PRSS1 were 60%, 25% and 5%, respectively. Conclusions As compared with previous studies, our patient cohort, with a relatively higher frequency of R122H mutation, showed a much lower surgery rate, and endoscopic interventions may be recommended to be the first-line treatment.